Sosialisasi Pentingnya Peran Orang Tua dalam Mendampingi Anak Selama Pembelajaran Daring - Ayu Ismi Hanifah (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
During the Covid-19 pandemic, the teaching and learning process is encouraged to be carried out online at home. This online learning activity needs more assistance, especially parents who are at home. The role of parents at home is very important and necessary, because the learning process affects the quality of learning outcomes. This service aims to provide education regarding the role of parents in assisting early childhood education children in online learning during the Covid-19 pandemic. The method used is socialization to parents of early childhood. The result of this service activity is to provide knowledge and understanding for parents in accompanying children during online learning for early childhood education. The activeness of parents in accompanying children is a determinant of the extent to which children's learning activities will have a positive impact on children's development.